Understanding community willingness to participate in community-based sanitation programs: Insights from Labuan Bajo, Indonesia - Sofiyah Evi Siti; Rafida Hanifa Athaya; Caesarina Naila Putri (BIO Web of Conferences)
This study investigates factors influencing community participation in adaptive environmental management programs in Labuan Bajo, Indonesia. Data from 477 residents were analyzed using binary logistic and probit regression models to evaluate the significance of sanitation infrastructure and community engagement. Results show that the presence of septic tanks (p<0.05 Logit; p<0.01 Probit) and proper maintenance (p<0.05 in both models) significantly enhance participation, emphasizing the importance of robust sanitation systems. Public toilets also positively impact participation (p<0.01 Logit; p<0.05 Probit), underscoring their role in public health promotion. Conversely, fecal sludge management shows no significant effect, highlighting a need for greater awareness. Community engagement is pivotal, with membership in local organizations (p<0.01 Logit; p<0.05 Probit) and involvement in sanitation teams (p<0.01 in both models) positively influencing participation. Educational outreach, particularly extension services (p<0.001 in both models) and training (p<0.01 in both models), emerges as a key driver, demonstrating the importance of knowledge dissemination. These findings offer actionable insights for policymakers to enhance community involvement in sanitation programs, particularly in coastal regions with similar characteristics.